A combined oral contraceptive affects mucosal SHIV susceptibility factors in a pigtail macaque (Macaca nemestrina) model. Issue 2 (23rd December 2014) - Dietz Ostergaard, Sharon; Butler, Katherine; Ritter, Jana M.; Johnson, Ryan; Sanders, Jeanine; Powell, Nathaniel; Lathrop, George; Zaki, Sherif R.; McNicholl, Janet M.; Kersh, Ellen N.
Abstract Background Injectable hormonal contraception may increase women's risk of HIV acquisition and can affect biological risk factors in animal models of HIV. We established, for the first time, a model to investigate whether combined oral contraceptives (COC) alter SHIV susceptibility in macaques. Methods Seven pigtail macaques were administered a monophasic levonorgestrel (LNG)/ethinyl estradiol (EE) COC at 33% or 66% of the human dose for 60 days. Menstrual cycling, vaginal epithelial thickness, and other SHIV susceptibility factors were monitored for a mean of 18 weeks. Results Mean vaginal epithelial thicknesses were 290.8 μm at baseline and 186.2 μm during COC (P = 0.0141, Mann–Whitney U‐test). Vaginal pH decreased from 8.5 during treatment to 6.5 post‐treatment (0.0176 two‐tailed t‐test). Measured microflora was unchanged. Conclusions COC caused thinning of the vaginal epithelium and vaginal pH changes, which may increase SHIV susceptibility. 0.033 mg LNG + .0066 mg EE appeared effective in suppressing ovulation.